Clinical Outcomes of Culture‐Negative and Culture‐Positive Periprosthetic Joint Infection: Similar Success Rate, Different Incidence of Complications. Issue 7 (9th June 2022) - Xu, Zhiyang; Huang, Changyu; Lin, Yiming; Chen, Yongfa; Fang, Xinyu; Huang, Zida; Zhang, Chaofan; Zhang, Zhenzhen; Zhang, Wenming
Abstract : Objective: To compare the clinical outcomes of culture‐negative periprosthetic joint infection (CN PJI) with those of culture‐positive periprosthetic joint infection (CP PJI). Methods: This study retrospectively examined data from 77 patients who underwent revision surgery due to periprosthetic joint infection (PJI) after hip and knee arthroplasty at our center from January 2012 to June 2017. There were 37 males and 40 females, with an average age of 63.6 year. All patients were classified by Tsukayama type, according to the bacterial culture results of synovial fluid and pre‐ and intraoperative tissues, 24 cases were included in the CN PJI group, and 53 cases were included in the CP PJI group. All patients underwent routine blood tests, liver, renal function tests, erythrocyte sedimentation rate (ESR) and C‐reactive protein (CRP) measurements. The remission rates of CN PJI and CP PJI were compared. The effects of the culture results on the curative effect were further compared by survival analysis. Results: The patients were followed regularly with an average of 29.2 months (range, 12–76 months). In total, there were 24 cases of CN PJI, with an incidence of 29.63%. The overall success rate of CN PJI group was 86.4% (19/22), and overall success rate of CP PJI group was 87.5% (42/48). The relative efficacy of various surgical options was: one‐stage revision 100% (7/7), two‐stage revision 96.3% (26/27), debridement and implant retention 64.3% (9/14), respectively. There was no significant difference in the success rate between the CN PJI group and the CP PJI group. The incidence of antibiotic‐related complications for the CN PJI group was significantly higher than that of the CP PJI group, with 58.3% for CN PJI and 11.3% for CP PJI, respectively. Conclusion: When CN PJI was treated according to the strict standards for the diagnosis and treatment, the success rate of treatment for the CN PJI group was similar to that for the CP PJI group. The incidence of antibiotic‐related complications from the CN PJI group was higher than that from the CP PJI group. Abstract : This study showed that if CN PJI patients were treated strictly according to Tsukayama type, with a combination of 2–6 weeks of intravenous vancomycin and ceftazidime or carbapenem antibiotic administration with oral quinolone antibiotics for 6–10 weeks, the overall success rate was similar to that of CP PJI, and there was no significant difference between the success rates of various surgical strategies in CN PJI and CP PJI.